Analisis Epistimologi Zakat dalam Perspektif Fiqih - Hamdan Ladiku (Pascasarjana IAIN Sultan Amai Gorontalo, 2020)
This study aims to analyze the epistemology of zakat in the perspective of fiqh. The reality of Muslims shows an imbalance between the awareness of tithe and the understanding of zakat fiqh. so the vision of zakat changing mustahik into muzakki cannot be optimized. The method used is library research, with qualitative descriptive analysis techniques. The results showed that zakat was intended as